Therapist, client factors, and efficacy in Cognitive Behavioural Therapy: A meta-analytic exploration of factors that contribute to positive outcome - Di Giulio, Gina (University of Ottawa (Canada), 2007)
A meta-analysis of the effectiveness of Cognitive Behavioural Therapy (CBT) for adult depression was conducted. Twenty-nine studies were identified from 1988 to 2004 that met selection criteria. Comparisons to no treatment, antidepressant medication, behaviour therapy, and other psychotherapies were made using Hedges' d corrected for sample size. Results indicated a clear superiority of cognitive therapy (CT) and CBT over wait-list or no treatment conditions, and slightly larger effect sizes for CT/CBT over pharmacological and other psychotherapeutic treatments for depression. As tests of homogeneity were not met for the pharmacotherapy and other psychotherapy conditions, the results should be interpreted with caution. About equal effect sizes were found between CT/CBT and Behavioural Therapy. Effect size was significantly related to format of treatment (with group therapy achieving a larger effect size than individual therapy format) and type of research trial (with larger effect sizes yielded for efficacy than effectiveness trials). Length of therapy, measured in weeks, was also significantly related to better outcome in CT/CBT. These results confirm that CT and CBT are excellent options for the treatment of adult depression.
Keywords: Psychology, Clinical.